Volume 2: Aircraft Engine; Marine; Microturbines and Small Turbomachinery 1992
DOI: 10.1115/92-gt-410
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties Evaluation of Generation-I SX-SiC

Abstract: Mechanical properties of a developmental high strength and high toughness SiC, Generation I SX, have been evaluated under a Department of Energy (DOE)/Oak Ridge National Laboratory (ORNL) subcontract. The mechanical properties determined included flexural strength, tensile strength, and fracture toughness at room and elevated temperatures. Stress rupture, dynamic fatigue and creep at elevated temperatures also have been evaluated. The strength limiting factors have been identified at room and elevated temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

1993
1993
1993
1993

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 4 publications
2
3
1
Order By: Relevance
“…Moreover no slow crack growth was evidenced at 1232°C since no strength drop at lower stress rates was observed. This observation is consistent with the earlier published results for the same material [2]. Hence the room temperature flexural strength (MOR) was considered to be the primary response for different densification conditions.…”
Section: Optimization Of Densification Conditionssupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover no slow crack growth was evidenced at 1232°C since no strength drop at lower stress rates was observed. This observation is consistent with the earlier published results for the same material [2]. Hence the room temperature flexural strength (MOR) was considered to be the primary response for different densification conditions.…”
Section: Optimization Of Densification Conditionssupporting
confidence: 92%
“…It is interesting to note that higher strength was observed with lower sintering temperatures and also corresponded to fewer volume flaws or "pools". The "pool" of second phase clusters appeared to form due to the reaction of SiC with yttrium aluminate as suggested by Omori [5] and from the Scanning Auger Electron Microscopic studies on the same material reported previously [2]. It is believed that at lower processing temperatures, the reaction is not severe enough to form many, large "pools".…”
Section: Densification Conditions Optimizationsupporting
confidence: 61%
See 3 more Smart Citations